Attainment of parenting goals in an Early Head Start program - Jameson, Julie S., author; Lehmann, Jean, advisor; Fidler, Deborah, advisor (Colorado State University. Libraries, 2008)
Early childhood programs providing parenting education and support seek to enhance home environments through comprehensive services aimed at developing nurturing relationships between parents and children. The majority of programs aimed at improving child and parent outcomes utilize the home visit as the primary means of service delivery. Home visit practitioners plan activities implemented in the family home designed to enhance child development while at the same time modeling and coaching the parent in their interactions with the child. The process of impacting child and family outcomes begins with the transfer of skills from home visitor to parent who in turn utilizes the skills to improve interactions and outcomes for the child. Early Head Start (EHS) is one of the five largest programs serving young children in the United States that utilizes the home visit approach in the delivery of services to pregnant women, infants, toddlers, and their families. In the city and surrounding communities of Fort Collins, Colorado, the Poudre School District (PSD) serves as the grantee agency for the delivery of EHS services. PSDEHS programs utilize family mentors to conduct the home visit and parent education portion of the program. Family mentors are responsible for the planning, implementing, and assessing of all home visit activities. This study documented parental progress toward goals identified by the parent and PSDEHS family mentor during participation in the home visiting program to assess factors that may contribute to success in goal attainment. Fifty-three families participated in the study over 12 weeks. Family mentors utilized the method of Goal Attainment Scaling (GAS) at each home visit to measure parental progress on jointly identified goals. GAS scores range from a score of -2 (much less than expected outcome) to +2 (much more than expected outcome). Identified goals fell into one of six general categories: family, financial, parenting, education/job, health/wellness, and other. Participants most often set family related and parenting related goals indicating those areas as needing improvement. GAS results indicated that while the majority of families scored below the expected outcome, all families scored within the range of -1 (somewhat less than expected outcome) and +1 (somewhat more than expected outcome). GAS scores tended to increase toward the positive range with an increase in the number of home visits received. Analysis of GAS scores among the various demographic groups present in PSDEHS revealed that home-based families had slightly higher mean GAS scores (m=-.36) than center-based families (m=-.40). Spanish speaking families had higher mean GAS scores (m=.07) than English speaking families (m=-.49). Teen parented families has slightly higher mean GAS scores (-.26) than adult parented families (m=-.36). As expected, dual parent families had higher mean GAS scores (m=-.26) than single parent families (-.52). Mean GAS scores also improved as the educational levels of mother's and father's increased.
Keywords: Early Head Start; goal attainment scaling; home visits; parenting; early childhood education; individual and family studies; parents and parenting; Head Start project